ANALYSIS OF THE NEED FOR DEVELOPING THE RANI LEARNING MODEL TO IMPROVE DESCRIPTIVE WRITING SKILLS - Rani Asriyani; Dian Indihadi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study was motivated by the low level of descriptive writing skills among elementary school students, particularly in terms of idea development, paragraph organization, and spelling accuracy, as identified through a preliminary study in the fourth grade at SDN Pasirjaya. The learning environment, which is still oriented toward final results without focusing on the writing process, has resulted in students being unable to write systematically and elaboratively. This study aims to analyze the need to develop the RANI (Readiness, Analyze, Name, Interpret) Learning Model as the basis for designing a process-based writing learning model. The research used a qualitative approach with a preliminary study design (needs analysis). Data sources included 28 fourth-grade students and 12 teachers at SDN Pasirjaya, with data collection techniques in the form of diagnostic tests, learning observations, interviews, and documentation. The data were analyzed descriptively through reduction, presentation, and conclusion drawing. The results showed that 43% of students were in the category of adequate writing ability, 29% were poor, and only 28% were good, with an average score of 68. These findings indicate the need for a structured, explicit, and process-based learning model as the basis for developing the RANI Model in the next stage of research.